34. THE ROLE OF TRADITIONAL MEDICINE IN THE TREATMENT OF INSOMNIA: A SCOPING REVIEW (Vietnam Journal of Community Medicine, 2025)
Objective: This study provides a scoping overview of the role of Traditional Medicine in the treatment of insomnia in Vietnam.Methods: A scoping review was conducted by searching for scientific articles published in Vietnam within the past 10 years, using the Ministry of Science and Technology’s database. The review followed the PRISMA-ScR (Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews) guidelines.Results: Among 12 published articles, most were clinical intervention studies comparing outcomes before and after treatment (n = 5), and one was an animal clinical trial (n = 1). The research materials included classical formulas or preparations derived from classical formulas (n = 4), and non-pharmacological interventions (n = 2).Conclusion: Over the past decade, research in Traditional Medicine for the treatment of insomnia in Vietnam has mainly focused on evaluating the effectiveness of classical herbal formulas, often in combination with non-pharmacological methods. However, the number of such studies remains limited.
Keywords: Traditional medicine, insomnia.